Capturing and Analyzing Publication, Citation, and Usage Data for Contextual Collection Development. Issue 1 (31st May 2018) - Pastva, Joelen; Shank, Jonathan; Gutzman, Karen E.; Kaul, Madhuri; Kubilius, Ramune K.
ABSTRACT: Librarians from the Galter Health Sciences Library at Northwestern University's Feinberg School of Medicine undertook a citation analysis study in early 2017 to supplement traditional electronic journal usage data in the hopes of more effectively demonstrating journals' value. The authors developed a methodology for gathering comprehensive publication and citation data for authors affiliated with the Feinberg School of Medicine, using Web of Science as the primary data source. Using this data, various metrics were employed to measure and evaluate journals in institutional and field-specific contexts, including co-citation networks, and increases or decreases of references over time per title. These metrics were compared against more traditional tools like Counting Online Usage of Networked Electronic Resources usage reports, cost-per-use analysis, and interlibrary loan statistics, to identify correlations and discrepancies. This use case demonstrates the potential value of incorporating publication and citation metrics into library collection development and evaluation practices.